The effects of mobile technologies on the level of student involvement - Abazova, Ludmila; Gutaeva, Zhansurat; Kochesokova, Madina (Institute of Advanced Engineering and Science, 2024)
In the modern world, there is a conscious interest in improving education quality with the help of modern information technologies. Innovative m-learning technology expands the possibilities and increases the effectiveness of training. Experiments conducted in European countries showed that the use of mobile devices positively affected academic performance, discipline, and interpersonal relationships among participants in the educational process. However, currently, practical research only generally concerns the issue of increasing foreign student involvement in the educational process. The purpose of the study is to experiment and obtain new data confirming the effectiveness of mobile technologies in increasing foreign student involvement in the educational process. The developed mobile technology-based course was introduced into the educational system of the university. The program included traditional and practical classes. The study confirms the effectiveness of mobile learning technology. A statistical data analysis showed positive dynamics in the indicators of the experimental group. The final data of the experimental group differed significantly from the initial ones: the average indicator of 2.9 (average involvement level) increased to 4 (+1.1). Based on the developed course using mobile learning, it is possible to create and practically implement new educational programs for universities.